Combination effects of anticholinesterasics in acetylcholinesterase of a fish species: effects of a metallic compound, an organophosphate pesticide, and a pharmaceutical drug - Nunes, Bruno
The simultaneous presence of distinct compounds in the aquatic environment can be causative of various toxicological interactions. This scenario challenges ecotoxicologists, since the assessment of toxicological effects caused by the simultaneous presence of multiple substances is by far more complicated. An illustrative example can be given by mentioning the anticholinesterasic compounds: by studying the level of cholinesterase impairment of an exposed organism, it is possible to ascertain the level of exposure to all anticholinesterasics (despite their chemical classes and natures) that the organism was subjected to. In this work, we describe the effects of three chemically different, albeit mechanistically, and toxicologically similar compounds (copper, chlorfenvinphos, and pyridostigmine) on cholinesterases of the fish Gambusia holbrooki. The results showed that the combinatorial effects may be of considerable extent, even for levels of exposure that are close to the ones already reported in the wild, for each isolated compound.